INTEGRATIVE MODELS AS A MEANS OF DEVELOPING VOLITIONAL QUALITIES IN FUTURE TEACHERS (International Congress on Economics, Management and Business Studies, 2026)
This article states that the development of the strong-willed qualities of future teachers is one of the pressing problems of our time. The article also provides details on integrated models as well as the kinds of future teachers.
Keywords: integral models, strong-willed qualities, independence, hard work, self-confidence, self-management, patience, perseverance, courage.